Hubungan Fungsi Kepala Ruangan dengan Kinerja Perawat Pelaksana di Ruangan Rawat Inap RSUD Palangka Raya - Noor Hidayati; Karmitasari Yanra Katimenta; Henry Wiyono (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
One of the critical elements affecting nurse performance and impacting the quality of nursing services is the implementation of the head nurse's functions. This role must be effectively integrated into the healthcare system to motivate nurses to provide optimal patient care, thereby improving community health quality. This study aims to analyze the relationship between the head nurse's functions and the performance of bedside nurses in the inpatient wards at RSUD Palangka Raya. Method: This study employed a quantitative method with a correlational research type and a cross-sectional approach. The sampling technique used was total sampling, involving 34 respondents. Data collection was performed using a questionnaire, and statistical analysis was conducted using the Spearman Rank Correlation test. Results:The results of the Spearman Rank statistical test showed a significance value (2-tailed) of p = 0.00 with a level of significance of p < 0.05, indicating a relationship between the head nurse's functions and the performance of bedside nurses. The correlation coefficient was 0.685, reflecting a high or strong correlation. This positive relationship indicates that as the function of the head nurse improves, the performance of bedside nurses also increases. Therefore, the alternative hypothesis (Ha) is accepted, meaning there is a relationship between the head nurse's functions and the performance of bedside nurses. Conclusion: There is a significant relationship between the head nurse's functions and the performance of bedside nurses. It is recommended that the hospital provide training for head nurses on management functions.